2014
DOI: 10.3382/ps.2013-03831
|View full text |Cite
|
Sign up to set email alerts
|

Low-fiber alfalfa (Medicago sativa L.) meal in the laying hen diet: Effects on productive traits and egg quality

Abstract: This study was designed to determine the effects on laying performance and egg quality resulting from partial substitution of soybean meal (SBM) with low-fiber alfalfa (LFA; Medicago sativa L.) meal in the diet of early-phase laying hens. ISA Brown layers, 18 wk of age, were randomly allocated to 2 dietary treatments and fed for 10 wk. The hens were fed 2 wheat middling-based diets: a control diet, which contained SBM (15% of diet), and a test diet containing LFA (15% of diet) as the main protein source. Low-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
50
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 28 publications
11
50
0
4
Order By: Relevance
“…In ducks fed lucerne-supplemented diet (3, 6 and 9%), there were no differences in the body weight, average daily gains, mortality rate and feed intake compared with the control group (Jiang et al, 2012). Partial replacement of soyabean meal with lucerne in laying hen nutrition did not have adverse effects on production traits (Laudadio et al, 2014). There are only a few studies indicating a possible effect of lucerne addition on bone formation processes, which are essential for animal welfare (Yıldız and Alpay, 2008).…”
Section: Introductionmentioning
confidence: 83%
“…In ducks fed lucerne-supplemented diet (3, 6 and 9%), there were no differences in the body weight, average daily gains, mortality rate and feed intake compared with the control group (Jiang et al, 2012). Partial replacement of soyabean meal with lucerne in laying hen nutrition did not have adverse effects on production traits (Laudadio et al, 2014). There are only a few studies indicating a possible effect of lucerne addition on bone formation processes, which are essential for animal welfare (Yıldız and Alpay, 2008).…”
Section: Introductionmentioning
confidence: 83%
“…Egg yolk colour in laying hens is one of the major parameters for the quality of an egg and is an important criterion for consumers (Teoh et al 2015). Egg yolk colour is correlated with pigment content and ranges from yellow (e.g., lutein, zeaxanthin, apo-ester) to red (e.g., canthaxanthin, citraxanthin, astaxanthin) (Laudadio et al 2014). The use of yellow lupin seed meal in the feeding mixture resulted in a more distinct yellow/red egg yolk (Dvorak et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hens reared on alfalfa or clover need significantly less feed protein than confined hens [7]. In particular, alfalfa forage can supply carotene, vitamins and other nutrients, especially high amount of protein up to 19% as dry matter basis [61,62]. In addition, it was found that organically reared broilers may overcome growth impairments associated with methionine deficiency through foraging [63].…”
Section: Influence Of Feeding Forage On Poultry Egg and Meat Qualitymentioning
confidence: 99%
“…It was assessed that the poultry products from grass-fed flocks tend to have less total cholesterol and more vitamins A and E, as well as high omega-3, and an improved omega-3 to omega-6 ratio [67]. It was found that egg cholesterol decreased as alfalfa meal increased in a laying hen diet [62]. Studies demonstrated that hens with access to high-quality pasture had eggs with at least twice as much vitamins A and E and omega-3s, compared to hens having no access to different pastures [68][69][70][71].…”
Section: Influence Of Feeding Forage On Poultry Egg and Meat Qualitymentioning
confidence: 99%